Presepsi Masyarakat terhadap Kinerja Pemerintah Daerah Hasil Audit Badan Pemeriksa Keuangan (BPK) di Kabupaten Belu - Maria Yohana Oy Tae; Margareth Gramediana Taolin; Floresita Melin Tulasi; Dulce Maria Gisela Saka; Benediktus Maurisko Geong; Susana Purnamasari Baso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Public assessment of local government performance is closely linked to transparency and accountability in public financial management. In Belu Regency, although the local government has consistently obtained an unqualified opinion (WTP) from the Audit Board of Indonesia (BPK), public understanding of audit findings remains limited. This condition raises questions regarding how audit results influence public perceptions of government performance. This study aims to explore community perceptions of the Belu Regency Government’s performance based on BPK audit results and to examine the extent to which audit information is understood and utilized by the public. A descriptive qualitative approach was employed, with data collected through open-ended questionnaires administered to 30 purposively selected respondents from diverse social backgrounds. The data were analyzed using thematic analysis to identify recurring patterns and key themes. The findings indicate that while most respondents recognize the importance of BPK audits in promoting transparency and accountability, their knowledge of specific audit findings is generally superficial. Public evaluations of government performance tend to rely primarily on the achievement of the WTP opinion rather than on detailed audit recommendations. Overall, the community perceives the local government’s performance positively but emphasizes the need for improved dissemination of audit information and consistent follow-up on BPK recommendations to strengthen public trust.